FAKTOR KEPUASAN PELANGGAN COFFEE SHOP DI KOPIXEL JEMBER - Lilis Setyarini; Joko Widodo; Dwi Herlindawati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Customer satisfaction is important to maintain the existence of a coffee shop in the face of competition. This is because the coffee shop business can be found almost in various places, this is influenced by the culture of drinking coffee which has become a lifestyle in all circles. In order for a coffee shop to be able to compete and maintain its existence, it must be able to create customer satisfaction. Kopixel is a coffee shop that is always busy with visitors and is able to compete even though there are many similar coffee shop businesses. Based on the results of research on customer satisfaction of the Coffee Shop in Kopixel Jember is influenced by five factors, namely product, price, service, facilities, atmosphere. This research was conducted to describe Kopixel customer satisfaction which makes Kopixel busy with visitors and able to compete. This research uses a qualitative descriptive approach with the research subjects being Kopixel customers and Kopixel Jember managers. The data collection process was carried out by interviews. The resulting data was analyzed by means of data reduction, data presentation, drawing conclusions, then the data was tested by source triangulation.